Traveling Wave Solution in a Diffusive Predator-Prey System with Holling Type-IV Functional Response - Deniu Yang; Lihan Liu; Hongyong Wang (Abstract and Applied Analysis)
We establish the existence of traveling wave solution for a reaction-diffusion predator-prey system with Holling type-IV functional response. For simplicity, only one space dimension will be involved, the traveling solution equivalent to the heteroclinic orbits in R3. The methods used to prove the result are the shooting argument and the invariant manifold theory.